1990
DOI: 10.1177/030006059001800403
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-Release Theophylline in the Treatment of Nocturnal Asthma

Abstract: A total of 104 asthmatic patients with symptoms of asthma and/or a 'morning dip' in the peak expiratory flow rate (PEFR) who were receiving multiple therapies, including inhaled or oral steroids, were treated in addition once nightly with controlled-release theophylline in an 8-week double-blind, placebo-controlled cross-over study. Theophylline produced an improvement in symptoms of cough, wheeze, sleep disturbance and PEFR in the 73 completing patients compared to run-in and placebo treatment. Theophylline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Clinical studies have shown salmeterol 15 and theophylline 18,19 to be safe and effective in treating nocturnal asthma. In a comparison of the two medications, salmeterol was superior to sustained-release theophylline in some objective measures of efficacy and was reported to be better tolerated by study patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have shown salmeterol 15 and theophylline 18,19 to be safe and effective in treating nocturnal asthma. In a comparison of the two medications, salmeterol was superior to sustained-release theophylline in some objective measures of efficacy and was reported to be better tolerated by study patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that both salmeterol xinafoate, [15][16][17] a highly selective, long-acting, inhaled bronchodilator, and theophylline, 18,19 an oral derivative of xanthine, decrease the incidence of nocturnal asthma symptoms and reduce early morning bronchoconstriction. The effects of inhaled ␤agonists and xanthine derivatives on sleep architecture and subjective sleep quality have been examined with inconclusive results.…”
mentioning
confidence: 99%
“…Clinical studies have suggested that theophylline acts as an anti-tussive in a range of conditions. In children and adults with poorly controlled asthma (Bose et al, 1987;Fairfax et al, 1990), theophylline significantly improved scores for cough and wheeze compared to placebo. Theophylline is also recommended for the treatment of cough in COPD (ACCP guidelines 2006) and has been shown to be effective for treating ACE-inhibitor related cough (Cazzola et al, 1993).…”
Section: Methylxanthinesmentioning
confidence: 97%